PLATO software provides analytic framework for investigating complexity beyond genome-wide association studies. Issue 1 (December 2017) - Hall, Molly; Wallace, John; Lucas, Anastasia; Kim, Dokyoon; Basile, Anna; Verma, Shefali; McCarty, Cathy; Brilliant, Murray; Peissig, Peggy; Kitchner, Terrie; Verma, Anurag; Pendergrass, Sarah; et al.
Abstract Genome-wide, imputed, sequence, and structural data are now available for exceedingly large sample sizes. The needs for data management, handling population structure and related samples, and performing associations have largely been met. However, the infrastructure to support analyses involving complexity beyond genome-wide association studies is not standardized or centralized. We provide the PLatform for the Analysis, Translation, and Organization of large-scale data (PLATO), a software tool equipped to handle multi-omic data for hundreds of thousands of samples to explore complexity using genetic interactions, environment-wide association studies and gene–environment interactions, phenome-wide association studies, as well as copy number and rare variant analyses. Using the data from the Marshfield Personalized Medicine Research Project, a site in the electronic Medical Records and Genomics Network, we apply each feature of PLATO to type 2 diabetes and demonstrate how PLATO can be used to uncover the complex etiology of common traits. Centralized infrastructure to support analyses involving complexity beyond genome-wide association studies is broadly needed. Here, Ritchie and colleagues develop PLATO, a software tool to process and integrate various methods for this task.